Psychometric Properties of the Short Form of the Fear of Cancer Recurrence Inventory (FCRI) in Chinese Breast Cancer Survivors - Peng, Li; Huang, Weirong; Zhang, Wenmo; Xu, Yuanyuan; Lu, Fang; Zhong, Ling; Chen, Xianchun; Xu, Song; Chen, Wenjun; Li, Min (Frontiers in Psychiatry, 2019)
Objective: Currently, fear of cancer recurrence (FCR) is emerging as an important issue for long-term breast cancer survivors and is associated with lower quality of life and functional impairment. Given that there is a dearth of research regarding the FCR of Chinese breast cancer survivors, this study investigated whether the short form of the Fear of Cancer Recurrence Inventory (FCRI) could detect high FCR and explored the level and characteristics of FCR in breast cancer survivors. Methods: Two hundred forty patients who had undergone successful breast cancer surgery in China submitted their survey through a website. The participants’ demographic and medical data, level of FCR, anxiety, depression and quality of life were assessed. Results: Two hundred and seven patients with ages ranging from 19 to 60 years completed the questionnaires. The mean FCR score of the total sample was 18.39. A cut-off score of 12 or higher on the short form of the FCRI was optimal for the detection of high FCR with a sensitivity of 98.6% and a specificity of 35%, and the PPV (positive predictive values) and NPV (negative predictive values) were 44% and 98%, respectively. The area under the curve of the ROC analysis was 83%. A total of 159 breast cancer survivors (76.81%) experienced high FCR levels (FCR score >12), characterized by lower functional and overall health than survivors with a low FCR (P<0.01). Conclusions: The short form of the FCRI is capable of detecting high FCR and is therefore able to assist Chinese breast cancer survivors in receiving appropriate care for reducing FCR.